Zhuangzi’s concept of harmony and its cultural implications - Maliavin, Vladimir V. V. (Acta Orientalia Vilnensia, 2008)
Tamkang University The ancient Daoist philosopher Zhuangzi (beginning of the 4th century BC), whose views comprise the core of the book ascribed to him, offers a profound concept of harmony, the basic condition of which is the differential relation within the continuity of universal change. Harmony for Zhuangzi is the predetermined or rather in-determined power of self-affection which constitutes the nature of life. As such it stands for the symbolic matrix of experience anticipating the world of things. This idea of harmony lies at the origin of creativity and style in culture. Zhuangzi’s philosophy is neither nihilistic nor apologetic in relation to actual cultures but provides, as it were, a comment on the conditions of the formation of culture.